2015
DOI: 10.2495/str150281
|View full text |Cite
|
Sign up to set email alerts
|

An innovative cathodic protection system for steel framed heritage structures

Abstract: The corrosion of early 20th century steel-framed buildings is resulting in serious damage to the integrity and appearance of many historically important structures. Since the application of cathodic protection to steel framed buildings in the late 1990s it has been proven to provide a low intrusive and aesthetically acceptable technique for the conservation of heritage structures.The principles of cathodic protection have not changed since its discovery by Humphry Davy in 1824 but have been adapted to a wide r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Meanwhile, carbon-based SFRG was used as an innovative cathodic protection (CP) system on historical steel framed buildings. This system was first applied at Leeds Civic Hall, a magnificent steel-framed, Portland stone clad Grade II-listed building that was built in 1933 [29]. The installation, comprising both the conductive geopolymer and a conventional rod anode CP system, was placed at the rear façade.…”
Section: Performance Of Geopolymer-strengthened Concrete Columnmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, carbon-based SFRG was used as an innovative cathodic protection (CP) system on historical steel framed buildings. This system was first applied at Leeds Civic Hall, a magnificent steel-framed, Portland stone clad Grade II-listed building that was built in 1933 [29]. The installation, comprising both the conductive geopolymer and a conventional rod anode CP system, was placed at the rear façade.…”
Section: Performance Of Geopolymer-strengthened Concrete Columnmentioning
confidence: 99%
“…Monitoring of the system showed that the geopolymer CP system achieved effective protection to the steel frame as the conventional CP system. Likewise, SFRG CP system was installed at the main entrance in a historic Kansas City building, Missouri, USA that was built in 1906 [29]. Although the facade remained in good condition, by the start of the new millennium it was showing signs of corrosion to the steel frame and cracking of the granite at the grand main entrance.…”
Section: Performance Of Geopolymer-strengthened Concrete Columnmentioning
confidence: 99%